Comparison of actions of m-nifedipine and nifedipine on isolated guinea pig atria and rabbit aortic strips - Wu Xiao-dong; Rao Man-ren (Acta Pharmacologica Sinica, 2016)
m-Nifedipine (m-Nif) had weaker inhibitory effects than nifedipine (Nif) on the staircase phenomenon, functional refractory period and contraction (IC50: m-Nif/Nif = 18) of isolated guinea pig left atria at concentrations of 0.1-1.0 mumol/L. At the same concentrations, both m-Nif and Nif could hardly change the post-rest potentiation, excitability and ectopic automaticity induced by epinephrine. m-Nif 0.05 mumol/L, had no effect on the automatic contractile force of isolated right atria but could slow down the automatic rhythm. On the contrary, Nif had little effect on the automatic rhythm but potently inhibited the contractile force. Furthermore, in isolated rabbit aorta strips, m-Nif had an equal or somewhat stronger inhibitory effect on the tension induced by KCl. These results suggest that m-Nif might be superior to Nif in treating myocardial ischemia, arterial hypertension and congestive heart failure.